From “Ought to Be” to “Being”: A Socio-Legal Analysis of the Conciliation Hearing in District of Barbalha/CE (Global Journal of Management and Business Research, 2024)
The present study aims from a participant observation to understand the so-called conciliation hearing and how it effectively occurs in the face of the dynamics of the Judicial Conflict Resolution Centers The analysis starts from the region of Barbalha seeking therefore tounderstand which issues permeate the realization of the conciliator yhearing that are not seen or noticed by the Law from its pragmatic and hegemonic logic of study and application Ethnographicinspired participant observation is the main tool for conducting this preliminary study